Using a sedimentation scanner to determine mangrove health responses to sedimentation derived from dredging. An example from northwestern Australia. Issue 12 (18th June 2018) - Mellor, Peter; Willson, Nicola; Claydon, Nadene; Paling, Erik I; Parker, Belinda; Wylie, Nicole; Mackey, Paul; Houridis, Harry
ABSTRACT: A sedimentation scanner was used to measure daily sediment height at 10 sites associated with a 14 million cubic metre dredging project in Port Hedland harbour, Western Australia, between July 2011 and May 2012. Data were collected from seven potential impact sites, where up to 35 mm of additional sedimentation was predicted via modelling to result from dredging and at three reference sites, where background variation was monitored. A variety of mangrove habitat health indices from each site (including leaf area and health, pneumatophore and faunal burrow density) were collected before, during and after dredging. Despite predictions, most impact sites received between 0 and 10 mm over the dredging period, with one site experiencing a gain of 28 mm. Reference sites received between 2 and 28 mm which was attributed to natural processes. It was concluded that the health of Avicennia marina (Forssk.) Vierh. and Rhizophora stylosa Griff., the most common mangroves, were neither affected by a net sedimentation up to 28 mm of over a period of 11 months (i.e. 30.5 mm y −1 ) nor rapid changes over shorter time periods such as 14 mm over two days. This technology could be deployed in any tidally influenced sedimentary environment where short-term processes were of interest.